The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11262-010-0565-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008

Abstract: To investigate the molecular epidemiology of Taiwanese Echovirus 30 (E-30) strains, we analyzed the 876 bp sequence of the VP1 gene from 32 Taiwanese strains isolated in 1988-2008, 498 reference sequences, and one Echovirus 21 strain as the out-group. Phylogenetic analysis detected six E-30 genotypes (designated GI-GVI) that had circulated globally during the past five decades. The genotypes varied widely in geographic distribution and circulation half-life. The GI, GII, and GV were ancient genotypes in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In the ECHO30 study, we found the average length for VP1 amplification to be 877 bp, which coded for 292 amino acids. It was reported that F122L, found mainly in the E30_h group, was thought to be one of the conserved positions of the drug-binding pocket [23]. Amino acid position 285, which is located at the end of the C terminal of VP1, was identified as variable (T285A) in our sequences.…”
Section: Discussionmentioning
confidence: 79%
“…In the ECHO30 study, we found the average length for VP1 amplification to be 877 bp, which coded for 292 amino acids. It was reported that F122L, found mainly in the E30_h group, was thought to be one of the conserved positions of the drug-binding pocket [23]. Amino acid position 285, which is located at the end of the C terminal of VP1, was identified as variable (T285A) in our sequences.…”
Section: Discussionmentioning
confidence: 79%
“…Using our sequencing data, we were able to successfully conduct a phylodynamic analysis on both the VP1 and 3D pol regions. The division of lineages into geographically or globally distributed tracts has also been reported in several other enteroviruses [ 38 , 39 ]. The analysis of VP1 revealed a stair-like (unbalanced) topology, which has also been observed in several other phylogenic investigations of enterovirus strains [ 13 , 40 ].…”
Section: Discussionmentioning
confidence: 76%
“…The present study provides phylogenetic evidence of earlier hypotheses suggesting that different lineages of a given EV type may have different transmission features and geographic distributions. The EV type E-30 genogroup VI (defined by Ke et al [ 52 ], also designated lineages d to h in [ 53 ]) has been reported in multiple worldwide outbreaks of acute meningitis over the last 15 years, in contrast to the re-emerging genogroup III (lineage a), which exhibited ‘endemic features’ in Russia [ 54 ]. Similar observations were derived from molecular epidemiology studies of two other infrequent EV types, E-3 and CV-B1.…”
Section: Discussionmentioning
confidence: 99%